Você está na página 1de 6

# Young’s, Minkowski’s, and Hölder’s inequalities

## September 13, 2011

Contents

1 Introduction 1

2 Young’s Inequality 2

3 Minkowski’s Inequality 3

4 Hölder’s inequality 5

1 Introduction

## The Cauchy inequality is the familiar expression

2ab ≤ a2 + b2 . (1)

## 0 ≤ (a − b)2 = a2 − 2ab − b2 (2)

which, after rearranging terms, is precisely the Cauchy inequality. In this note, we prove
Young’s inequality, which is a version of the Cauchy inequality that lets the power of 2
be replaced by the power of p for any 1 < p < ∞. From Young’s inequality follow the
Minkowski inequality (the triangle inequality for the lp -norms), and the Hölder inequalities.

1
2 Young’s Inequality

## When 1 < p < ∞ and a, b ≥ 0, Young’s inequality is the expression

p − 1 p−1
p 1
ab ≤ a + bp . (3)
p p
This seems strange and complicated. What good could it possibly be?

## The first thing to note is Young’s inequality is a far-reaching generalization of Cauchy’s

inequality. In particular, if p = 2, then p1 = p−1 1
p = 2 and we have Cauchy’s inequality:

1 2 1
ab ≤ a + b2 . (4)
2 2
Normally to use Young’s inequality one chooses a specific p, and a and b are free-floating
quantities. For instance, if p = 5, we get
4 5/4 1
ab ≤ a + b5 .
5 5
Before proving Young’s inequality, we require a certain fact about the exponential function.

## Lemma 2.1 (The interpolation inequality for ex .) If t ∈ [0, 1], then

eta+(1−t)b ≤ tea + (1 − t)eb . (5)

Proof. The equation of the secant line through the points (a, ea ) and (b, eb ) on the graph of
ex is precisely
t 7→ ta + (1 − t)b, tea + (1 − t)eb .

(6)
Obviously the graph of this line intersects the graph of ex at precisely two points: (b, eb )
when t = 0, and (a, ea ) when t = 1. To parametrize the graph of ex so that the x-value of
this parametrization and that of the parametrization of the secant line are the same, we use
 
t 7→ ta + (1 − t)b, eta + (1−t)b . (7)

But because ex is concave up, any secant line lies above the graph in between the points of
intersection. This means precisely that the y-values of these two parametrized curves obey
eta + (1−t)b ≤ t ea + (1 − t) eb , (8)
which was to be proved. 

Theorem 2.2 (Young’s Inequality) Assume a and b are real numbers, and p > 1. Then
p − 1 p−1
p 1
ab ≤ a + bp .
p p

2
Proof. There are a number of conceptually different ways to prove this inequality. Our
method will use Lemma 2.1. Writing

## ab = elog a + log b (9)

  ! !
p−1 p p−1 1
= Exp log a + 1− log b , (10)
p p−1 p 1 − p−1
p

## from Lemma 2.1 we get

    ! !
p−1 p p−1 1
ab ≤ Exp log a + 1− Exp log b (11)
p p−1 p 1 − p−1
p
 
p−1 p 1
= Exp log a + Exp (p log b) (12)
p p−1 p
p − 1 p−1
p 1
= a + bp . (13)
p p

3 Minkowski’s Inequality

## Theorem 3.1 (Minkowski’s Inequality) If 1 ≤ p < ∞, then whenever X, Y ∈ VF we

have

kX + Y kp ≤ kXkp + kY kp . (14)

## Proof. To prove that kX + Y kp ≤ kXkp + kY kp , we will replace Y by tY , and use the

observation that
Z 1
d
kX + Y kp − kXkp = kX + tY kp dt (15)
0 dt
Z 1
d
kXk + kY kp − kXkp = (kXkp + tkY kp ) dt (16)
0 dt

## and then all we need to prove is that

d d
kX + tY kp ≤ (kXkp + tkY kp ) , (17)
dt dt
which is actually simpler. Note that the right side of (17) is just kY kp . Computing the left

3
side is slightly tougher:

! p1
d d X
kX + tY kp = |xi − tyi |p (18)
dt dt i=1

! 1−p
p ∞
X X
p
= |xi − tyi | |xi − tyi |p−1 · sgn(xi − tyi ) · yi (19)
i=1 i=1

X
= kX − tY k1−p
p · |xi − tyi |p−1 · sgn(xi − tyi ) · yi . (20)
i=1

## But of course sgn(xi − tyi ) · yi ≤ |yi |, so we have

∞  p−1
d X |xi − tyi |
kX + tY kp ≤ |yi |. (21)
dt i=1
kX − tY kp

To proceed from here, we manipulate this expression so that eventually we can use Young’s
inequality to our advantage. We have
∞  p−1
d X |xi − tyi | |yi | p−1
p
kX + tY kp ≤ p−1 kY kp (22)
dt kX − tY k p p
i=1 kY kp
∞  p−1
X |xi − tyi | 1
|yi |
= kY kpp · p−1 . (23)
kX − tY k p
i=1 kY kp p

## When p = 1 we get directly that

d X
kX + tY k1 ≤ |yi | (24)
dt i=1
= kY k1 (25)
d
= (kXk1 + tkY k1 ) (26)
dt
as desired. When 1 < p < ∞ we apply Young’s inequality to get
 p
 p 
∞  (p−1) p−1
d X p − 1 |x i − tyi | 1
1 |yi |
kX + tY kp ≤  kY kpp +  p−1
  (27)
dt p kX − tY k p p p
i=1 kY kp
∞ ∞
p − 1 X |xi − tyi |p 1 X |yi |p
= p kY kp + (28)
p i=1 kX − tY kp p i=1 kY kpp−1
∞ ∞
! !
p−1 kY kp X
p 1 1 X
p
= · |xi − tyi | + · |yi | (29)
.
p kX − tY kpp i=1 p kY kp−1
p i=1

4
P∞ P∞
Finally note that i=1 |xi − tyi |p equals precisely kX −tY kpp and i=1 |yi |p equals precisely
kY kpp . Therefore
   
d p−1 kY kp p 1 1 p
kX + tY kp ≤ · kX − tY k + · kY k (30)
dt p kX − tY kpp p
p kY kpp−1 p

p−1 1
= kY kp + kY kp (31)
p p
= kY kp . (32)

## Therefore, as desired, we have proved that

d d
kX + tY kp ≤ (kXkp + tkY kp ) , (33)
dt dt
so the theorem follows from (15) and (16). 

4 Hölder’s inequality

X
xi yi ≤ kXk p−1
p kY k .
p (34)
i=1

## Proof. By Young’s inequality we have

∞ ∞
X xi yi X |xi | |yi |
≤ (35)
i=1
kXk p−1
p kY kp i=1
kXk p−1
p kY kp
 
∞ p
p
X  p − 1 |xi | p−1 1 |yi | 
≤ + (36)
kY kpp
p
p p
 
p−1
i=1 kXk p
p−1
∞ ∞
p−1 1 X p 1 1 X
= |xi | p−1 + |yi |p (37)
p kY kpp i=1
p
p kXk p−1
p i=1
p−1

p−1 1
= + (38)
p p
Thus we have shown that
∞ ∞
1 X X xi yi
xi yi = (39)
kXk p−1
p kY k
p i=1 i=1
kXk p−1
p kY kp
≤ 1, (40)

5
so after multiplying both sides by kXk p−1
p kY k
p we get

X
xi yi ≤ p kY k
kXk p−1 p (41)
i=1